2004
DOI: 10.1590/s1516-89132004000500016
|View full text |Cite
|
Sign up to set email alerts
|

Short-term cold storage of sperm from six neotropical characiformes fishes

Abstract: Sperm of the following Neotropical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 18 publications
1
25
1
6
Order By: Relevance
“…The motility values observed in the sperm of L. marmoratus showed that semen remained viable after cooling. These results corroborate those reported by Marques and Godinho (2004), which used cooled semen of Leporinus friderici for seven hours.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The motility values observed in the sperm of L. marmoratus showed that semen remained viable after cooling. These results corroborate those reported by Marques and Godinho (2004), which used cooled semen of Leporinus friderici for seven hours.…”
Section: Discussionsupporting
confidence: 92%
“…According to Marques and Godinho (2004) refrigeration is a simple and alternative technique that allows short-term utilization of fish sperm, thereby optimizing the fertilization of eggs and assuring a higher productivity in the breeding process. An additional advantage is the easy transportation in proper recipients such as plastic bags (Stoss and Refstie, 1983) and plastic tubes (Chereguini et al, 1997;Wayman et al, 1998), not requiring use of liquid nitrogen containers.…”
Section: Introductionmentioning
confidence: 99%
“…Após a mensuração do volume total de sêmen liberado por meio de um tubo de ensaio graduado, os gametas masculinos coletados foram posteriormente colocados em pequenos recipientes em caixas de isopor contendo gelo (Marques & Godinho, 2004) e conservados a temperatura média de 13 ºC. Em seguida, foi realizada a mistura do sêmen proveniente de todos os reprodutores, originando um pool de sêmen.…”
Section: Methodsunclassified
“…O índice de sobrevivência espermática foi mensurado pelo método de coloração eosina-nigrosina (Murgas et al, 2003), porém com 30 μL de sêmen e 90 μL de cada corante, para realização de uma mistura e confecção do esfregaço. Após o processamento das lâminas, o material foi analisado em microscópio de luz em objetiva de 40×, contando-se um número total de 400 espermatozoides, no qual células mortas apresentaram-se rosadas, em decorrência da absorção dos corantes, e as vivas apresentaram-se brancas, por serem impermeáveis aos corantes.…”
Section: Methodsunclassified
“…Besides being cheap and practical, this technique application can ensure the productivity of fingerling producing stations, and it can utilize semen in several females which may come spawning at different times (Marques & Godinho, 2004;Zaniboni-Filho & Nuñer, 2004).…”
Section: Diferentes Soluções Diluidoras Para O Resfriamento Do Sêmen mentioning
confidence: 99%